1990
DOI: 10.1016/s0006-291x(05)80095-6
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophils exhibit disparate chemotactic factor gene expression

Abstract: The evolution of acute inflammation from initiation through resolution is associated with the changing character of the infiltrating leukocytes. Recruitment of these leukocytes is dependent upon the generation of chemotactic factors that have either global or specific activity for a particular leukocyte. In this manuscript we present data demonstrating that human neutrophils can express mRNA for neutrophil chemotactic factor/interleukin 8 (IL-8), but fail to express mRNA for monocyte chemotactic protein (MCP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(57 citation statements)
references
References 20 publications
2
53
1
1
Order By: Relevance
“…1B) are: 1) the complete lack of CXCL10 mRNA induction by ultra pure LPS in neutrophils in contrast to LPS-treated monocytes; 2) the very modest capacity of IFN-␥ to up-regulate CXCL10 mRNA in neutrophils, unlike its strong effect in monocytes (Fig. 1A) (12,13); 3) the synergistic induction of CXCL10 mRNA by ultra pure LPS and IFN-␥ in neutrophils (12, 13); 4) the potent effect of IFN-␥ on CD64 mRNA expression in neutrophils (37); 5) the biphasic effect of IFN-␥ on TNF-␣ and CCL4 (data not shown) mRNA expression in ultra pure LPS-treated neutrophils (38, 39); 6) the lack of induction of IL-6 and CCL2 (data not shown) mRNAs by ultra pure LPS in neutrophils that confirms earlier observations (8,40,41) and that also excludes any influence of possible contamination of monocyte RNA in our neutrophil preparations (8,42). Similar results were observed with a second ultra pure LPS, certified as being ineffective toward TLR4-deficient mouse cells by the supplier (Alexis).…”
Section: Effect Of Ultra Pure Lps On the Expression Of Cxcl10 And Othsupporting
confidence: 79%
See 1 more Smart Citation
“…1B) are: 1) the complete lack of CXCL10 mRNA induction by ultra pure LPS in neutrophils in contrast to LPS-treated monocytes; 2) the very modest capacity of IFN-␥ to up-regulate CXCL10 mRNA in neutrophils, unlike its strong effect in monocytes (Fig. 1A) (12,13); 3) the synergistic induction of CXCL10 mRNA by ultra pure LPS and IFN-␥ in neutrophils (12, 13); 4) the potent effect of IFN-␥ on CD64 mRNA expression in neutrophils (37); 5) the biphasic effect of IFN-␥ on TNF-␣ and CCL4 (data not shown) mRNA expression in ultra pure LPS-treated neutrophils (38, 39); 6) the lack of induction of IL-6 and CCL2 (data not shown) mRNAs by ultra pure LPS in neutrophils that confirms earlier observations (8,40,41) and that also excludes any influence of possible contamination of monocyte RNA in our neutrophil preparations (8,42). Similar results were observed with a second ultra pure LPS, certified as being ineffective toward TLR4-deficient mouse cells by the supplier (Alexis).…”
Section: Effect Of Ultra Pure Lps On the Expression Of Cxcl10 And Othsupporting
confidence: 79%
“…A5060) Abs were from Sigma-Aldrich. Polyclonal Abs to NF-B-activating kinase-associated protein 1 (NAP1) were generated by immunization of mice with a synthetic peptide corresponding to the residues S 27 IYSGDESVASHFA 40 of human NAP1 (20) according to standard procedures. Anti-TLR4 and anti-TLR2 neutralizing Abs were provided, respectively, by Dr. Olsen (NovImmune) (21) and Dr. T. Musso (University of Turin, Turin, Italy) (22).…”
Section: Antibodiesmentioning
confidence: 99%
“…[23][24][25][26] IL-8 is an inflammatory cytokine with a strong effect on neutrophil activation and chemotaxis. 27,28 Early evidence for the involvement of this chemokine in allergic inflammation was obtained from a study that demonstrated that cultured bronchial epithelial cells derived from asthmatic subjects released IL-8 into culture supernatant.…”
Section: Discussionmentioning
confidence: 99%
“…Although many chemoattractants for human neutrophils have been described, there has been recent interest in the CXC chemokines, including IL-8, ENA-78, and growth-related oncogene ␣, ␤, and ␥ (17)(18)(19). Chemokines bind to glycosaminoglycan-containing proteoglycans, which are present on endothelial cells and in the extracellular matrix (20,21).…”
Section: P Lasminogen Activator Inhibitor-1 (Pai-1)mentioning
confidence: 99%